Constituting Religion Islam, Liberal Rights, and the Malaysian State - Moustafa, Tamir (Social Sciences, 2018)
Constituting Religion examines how activists work to expand or challenge the reach of the shariah court system, and how these legal struggles shape popular understandings of Islam, liberal rights. This title is also available as Open Access.